2015
DOI: 10.2220/biomedres.36.47
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of plantar subcutaneous administration of bergamot essential oil and linalool on formalin-induced nociceptive behavior in </b><b>mice </b>

Abstract: This study investigated the effect of bergamot essential oil (BEO) or linalool, a major volatile component of BEO, on the nociceptive response to formalin. Plantar subcutaneous injection of BEO or linalool into the ipsilateral hindpaw reduced both the first and late phases of the formalininduced licking and biting responses in mice. Plantar subcutaneous injection of BEO or linalool into the contralateral hindpaw did not yield an antinociceptive effect, suggesting that the antinociceptive effect of BEO or linal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Another fundamental facet is the increase of pain states in demented patients that are particularly related to agitation and aggression [16]. There is promising evidence for the effectiveness of aromatherapy for managing chronic pain: it was demonstrated that the intraplantar administration of Bergamot Essential Oil (BEO), a citrus fruit belonging to the Rutaceae family, significantly attenuates capsaicin-induced nociceptive behaviour [63] and both the first and the second phase of formalin-induced nocifensive response, thus confirming the previous observation that BEO reduces mechanical allodynia in neuropathic pain models [6466]. Therefore, more rigorous RCTs assessing the effectiveness of aromatherapy on BPSDs, with recruitment of larger samples of patients and longer duration, are needed [21].…”
Section: Conclusion and Future Perspectivessupporting
confidence: 61%
“…Another fundamental facet is the increase of pain states in demented patients that are particularly related to agitation and aggression [16]. There is promising evidence for the effectiveness of aromatherapy for managing chronic pain: it was demonstrated that the intraplantar administration of Bergamot Essential Oil (BEO), a citrus fruit belonging to the Rutaceae family, significantly attenuates capsaicin-induced nociceptive behaviour [63] and both the first and the second phase of formalin-induced nocifensive response, thus confirming the previous observation that BEO reduces mechanical allodynia in neuropathic pain models [6466]. Therefore, more rigorous RCTs assessing the effectiveness of aromatherapy on BPSDs, with recruitment of larger samples of patients and longer duration, are needed [21].…”
Section: Conclusion and Future Perspectivessupporting
confidence: 61%
“…Untreated pain is a major contributor to reduced quality of life and disability in dementia patients, and can lead to increased behavioural and psychological symptoms of dementia (BPSD) [ 59 , 60 ]. Therefore, the behavioural effects reported herein in conjunction with its established analgesic properties [ 13 , 14 , 15 , 16 , 17 , 18 ] could provide the rational basis to the use of BEO at reducing BPSD associated with dementia.…”
Section: Discussionmentioning
confidence: 96%
“…BEO is used to facilitate wound healing as antiseptic and antihelminthic, effects that are supported by antimicrobial [ 5 ] and antifungal [ 6 ] activities as well as the capacity of the phytocomplex to increase oxidative metabolism in human polymorphonuclear leukocytes [ 7 ]. Furthermore, data accumulated in the literature so far indicate that bergamot oil is endowed with notable neurobiolological effects (see [ 8 , 9 ]) originating, at least in part, by an interference with basic mechanisms finely tuning synaptic plasticity under physiological [ 10 , 11 ] as well as pathological conditions, i.e., brain ischemia [ 12 ] and pain [ 13 , 14 , 15 , 16 , 17 , 18 ], induced under controlled and broadly validated experimental settings. Interestingly, BEO also showed neuroprotective effects in human neuroblastoma cell line [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aromatherapy using an essential oil endowed with strong analgesic properties could be even more useful in the management of BPSDs as agitation [69]. BEO has been proven to exert analgesic activity both in inflammatory [70][71][72] and in neuropathic [73,74] pain models, also via inhalatory route of administration [75]. The analgesic properties of BEO are reported in Table 1.…”
Section: Novel Pharmacological Mechanisms For Npss Of Dementia Clinicmentioning
confidence: 99%
“…Plantar subcutaneous [72]. BEO (10 µg) significantly inhibited the nociceptive response to 2% formalin, only in the ipsilateral side, and this effect was antagonized by naloxone hydrochloride and methiodide [72]. Katsuyama et al, 2015 [72].…”
Section: Novel Pharmacological Mechanisms For Npss Of Dementia Clinicmentioning
confidence: 99%